Merawat ingatan peristiwa genosida dan dominasi VOC di Banda tahun 1621 (dalam perspektif sosial-ekonomi) - Nur Isma Lailiyah; Ana Khairunnisaa; Elizabeth Dewi Ekaristiningrum (Universitas Negeri Malang, 2021)
This article discusses the Genocide and VOC domination in Banda in 1621 by examining it from a socio-economic perspective. Nutmeg, the main commodity of the Banda Islands in Central Maluku, has become a commodity that is quite sought after by Europeans from the 15th to 19th centuries. The high price and the fall of Constantinople resulted in the exploration of shipping to find sources of spices started by the Europeans which came to be known as the Spice Route and making Banda the axis of the global economy. With such a strong appeal, the VOC ordered Admiral Jan Pieterszoon Coen (1587-1629) to control the clove and nutmeg commodity areas for the VOC either by negotiation or by force. This study aims to obtain an overview of the socio-economic conditions under the domination of the VOC in the Genocide incident in Banda. With this aim, in writing this article using the method of literature review through searching related historical sources. The results of this study obtained information that the socio-economic people of Banda experienced oppression, trade monopoly, prohibited the Banda people from carrying out a free trade system and the Banda people lived in disrespect of the VOC for their rights.Artikel ini membahas tentang peristiwa Genosida dan dominasi VOC di Banda tahun 1621 dengan mengkajinya berdasarkan perspektif sosial-ekonomi. Pala, komoditas utama Kepulauan Banda di Maluku Tengah ini menjadi komoditas yang cukup dicari oleh Bangsa Eropa sejak abad ke-15 sampai 19. Harganya yang tinggi dan jatuhnya Konstantinopel mengakibatkan eksplorasi pelayaran mencari sumber rempah dimulai oleh Bangsa Eropa yang kemudian dikenal sebagai pelayaran jalur rempah dan menjadikan Banda sebagai poros ekonomi global. Dengan daya tariknya yang begitu kuat VOC memerintahkan Laksamana Jan Pieterszoon Coen (1587-1629) untuk menguasai wilayah komoditas cengkeh dan pala untuk VOC baik dengan cara perundingan maupun kekerasan. Kajian ini bertujuan untuk memperoleh gambaran tentang sosial ekonomi di bawah dominasi VOC dalam peristiwa Genosida di Banda. Dengan tujuan tersebut, dalam penulisan artikel ini menggunakan metode kajian literatur melalui penelusuran sumber-sumber sejarah terkait. Hasil dari kajian ini memperoleh informasi bahwa sosial ekonomi rakyat Banda mengalami penindasan, monopoli perdagangan, melarang rakyat Banda melakukan sistem perdagangan bebas dan rakyat Banda hidup dalam ketidakhormatan VOC pada hak-hak mereka.